Re-membering the Black Atlantic : on the poetics and politics of literary memory - Eckstein, Lars (Cross/cultures, 2006)
The Atlantic slave trade continues to haunt the cultural memories of Africa, Europe and the Americas. There is a prevailing desire to forget: While victims of the African diaspora tried to flee the sites of trauma, enlightened Westerners preferred to be oblivious to the discomforting complicity between their enlightenment and chattel slavery. Recently, however, fiction writers have ventured to 're-member' the Black Atlantic. This book is concerned with how literature performs as memory. It sets out to chart systematically the ways in which literature and memory intersect, and offers readings of.